Gendering graffiti in Brazil. Issue 2 (26th May 2020) - Phua, Voon Chin
Abstract : Gender expressions in a person's daily rituals or representations in the media are critical in understanding gender relations. Studies on representations have generally focused those presented in textbooks and in advertisements. However, studies rarely examine gender representation in graffiti. In his analysis of advertisements, Goffman argues that advertisers do not create the ritualised expressions they employ but draw upon what we already know, and thus rendering readable images. Using the same logic, I posit that graffiti artists also base their images, at least in part, on socially readable and acceptable representations of gender. This effort may not be conscious and deliberate, but consistent with the social constructionist perspective, is an attempt to draw upon that with which we are familiar. As such, graffiti (like advertisements) become a source of data that we can analyse to examine gender representation. Examining graffiti in Brazil, I find graffiti with human images are present in two forms: cartoons, and life-portraits. Hyper-feminisation and sexualised images of women are prevalent. In contrast, images of men are less sexualised, particularly in terms of nudity. In addition, both the portrayal and interpretation of these images reflect a heterosexual bias.